The Use of Junior Weight Vest on Arm Strength in Junior Pencak Silat Athletes - Made Agus Dharmadi (Indonesian Journal Of Educational Research and Review, 2022)
Weight training for junior athletes is not recommended using heavy equipment at the fitness center. Junior athletes need weight training but use safe weights. This study analyzes the Junior Weight Vest (JWV) use on arm muscle strength in Junior Pencak Silat arts athletes. This type of research is descriptive quantitative, with an experimental design using a pre-test and post-test control group design. The sample of this study consisted of 20 randomly selected Junior Pencak Silat athletes with an age range of 10-15 years. The methods used in collecting data are observation, interviews, and instruments. The instrument used in collecting data is a questionnaire. Data analysis in this study used quantitative analysis using the Paired Sample T Test and Way ANOVA analysis. The study results show differences in the effect of those who use JWV on the arm muscle strength of Junior Pencak Silat athletes. Second, there is no difference in the effect of those who do not use JWV (Non-JWV) on the arm muscle strength of Junior Pencak Silat arts athletes. Third, there is a difference in the effect on the two groups. It was concluded that JWV in Pencak silat arts training had better results than those who did not use JWV (Non-JWV). The implications of this research are expected to be able to use JWV to improve other physical abilities such as speed, agility, power, and endurance.